Risk Factors and Clinical Characteristics of Severe Fever with Thrombocytopenia Syndrome - Wang, Fei (Int J Gen Med, 2020)
PURPOSE: This study was to investigate the clinical characteristics and laboratory parameters of severe fever with thrombocytopenia syndrome (SFTS). PATIENTS AND METHODS: A detailed retrospective analysis of clinical records for SFTS patients was conducted. Fifty-one cases confirmed SFTS virus infected were enrolled. The clinical characteristics and laboratory parameters between survivors and non-survivors were analyzed. RESULTS: All patients aged between 30 and 80 years were farmers or residing in wooded and hilly areas. All patients occurred between April and October. The major clinical manifestations were fever, fatigue, diarrhea, myalgia, nausea and vomiting. Conscious disturbance, lymph node enlargement and hemorrhage were common. Fatal outcome occurred in 31.4% (16/51) of patients. Compared with survivors group, in non-survivors group, the proportion of consciousness disturbance, age, the levels of AST, LDH, Bun, Cr, PT and APTT were significantly increased, and PLT was significantly decreased. The age, PLT, AST, LDH, Cr, PT and APTT were the risk factors for fatal outcomes. Moreover, the age (OR, 1.245; 95% CI, 1.052–1.474) and APTT (OR, 1.095; 95% CI, 1.005–1.192) were the independent risk factors for fatal outcomes. Heteromorphic lymphocyte and hemophagocytosis could be found in SFTS patients, especially the proportion of finding hemophagocytosis was significantly higher in non-survivors group compared with survivors group. CONCLUSION: These results suggest SFTS is a systemic infection, the age and APTT can be used as potential predictors referring to severe SFTS cases.